POLITICAL IMPLICATIONS AND JURISDICTIONAL CONFLICTS IN IMPLEMENTING THE 2023 HEALTH LAW ON THE MEDICAL PROFESSION IN INDONESIA - Pratama, Aditya (JOURNAL EQUITABLE, 2024)
The 2023 Health Law in Indonesia has sparked debate regarding its impact on the Collegium of Medicine and the Indonesian Medical Council (KKI). This paper examines the legal controversies surrounding these institutions within the context of the law. Employing a legal normative approach, the study analyzes health laws and scholarly literature to understand the implications of the 2023 Health Law on the roles and functions of the Collegium and KKI. Findings indicate significant changes in their authority and autonomy, raising concerns about medical education and practice quality. Government intervention and the marginalization of professional organizations pose threats to institutional independence and healthcare service quality. Recommendations include revising the law to restore Collegium and KKI authority while limiting government intervention to uphold constitutional rights. Strengthening communication between the government and medical professionals, enhancing public awareness, and empowering professional organizations are proposed solutions. This research emphasizes the need to balance government regulation with professional independence to ensure quality healthcare delivery in Indonesia.